An organisational culture and trustworthiness multidimensional model to engender employee creativity. Issue 4 (1st November 2018) - Ogbeibu, Samuel; Senadjki, Abdelhak; Luen Peng, Tan
Abstract : Purpose: The purpose of this paper is to elicit a conceptual understanding of the moderating effect of trustworthiness on the relationship between organisational culture and employee creativity. Design/methodology/approach: This study is theoretical in nature and draws conceptual insights from an integration of theoretical and conceptual underpinnings: the competing values framework, trustworthiness from the integrative model of organisational trust and the componential theory of individual creativity. Findings: Trustworthiness plays a major role in influencing the degree at which managers engender employee creativity. This study postulates that clan and adhocracy organisational culture dimensions have a positive impact on employee creativity, while market and hierarchy organisational culture dimensions have negative impacts on employee creativity. Employee creativity would be engendered if organisational cultures are tailored towards improving the ability of employees. Engendering of employee creativity is contingent on an acceptable degree of benevolence and integrity expressed between managers and their respective employees. Originality/value: By integrating several methodological underpinnings to produce a multidimensional model for engendering employee creativity, from the lens of a supportive organisational culture, this study offers novel insights for both managerial practice and actions.